Pengaruh Pengembangan Karir dan Beban Kerja Terhadap Loyalitas Pegawai dengan Stres Kerja Sebagai Variabel Intervening Pada Pada Balai Wilayah Sungai Sumatra V Padang - Gheans Vero; Vicky Brama Kumbara; Nia Nadilla (Jurnal Ekonomi dan Bisnis Digital, 2026)
Employee loyalty is one of the important factors in organizational success, particularly in public institutions with high demands for service and work responsibilities. Employee loyalty problems may be influenced by several factors, including career development, workload, and work stress. This study aims to analyze the effect of career development and workload on employee loyalty with work stress as an intervening variable at the River Basin Center of Sumatra V Padang. This research employed a quantitative approach using a survey method through questionnaires distributed to employees as research respondents. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS software. The results showed that career development had a negative and insignificant effect on work stress and employee loyalty. Workload had a positive and significant effect on work stress and employee loyalty. Furthermore, work stress had a positive and significant effect on employee loyalty. The mediation test revealed that work stress was unable to mediate the relationship between career development and employee loyalty but was able to mediate the relationship between workload and employee loyalty. This study implies that organizations need to manage workload and work stress effectively to improve employee loyalty